Сучасні тенденції розвитку аматорського футболу в Україні - Дорошенко, І.; Сватьєв, А.; Соболь, Е.; Данильченко, С.; Дорошенко, Едуард Юрійович; Doroshenko, I.; Svatyev, A.; Sobol, E.; Danylchenko, S.; Doroshenko, E. Yu. (My University, 2023)
Мета дослідження – аналіз і систематизація сучасного стану та узагальнення шляхів розвитку аматорського футболу в Україні з урахуванням регіональних аспектів за період 2018-2023 років. Методи дослідження: аналіз та узагальнення даних науково-методичних літературних джерел і мережі «Internet», педагогічні спостереження, контент-аналіз матеріалів офіційних сайтів обласних асоціацій футболу, асоціації аматорського футболу України, Української Асоціації Футболу, Міжнародної Федерації Футбольних Асоціацій (FIFA) за період 2018-2023 роки, методи математичної статистики. Результати. Проаналізовано кількісні показники представництва команд від регіональних асоціацій футболу в групових і фінальних турнірах чемпіонатів України з футболу серед аматорських команд за період 2018-2023 років. The purpose of the study is to analyze and systematize the current state and generalize the ways of development of amateur football in Ukraine, taking into account regional aspects for the period 2018-2023. Research methods: analysis and generalization of data from scientific and methodological literary sources and the Internet network, pedagogical observations, content analysis of materials of the official websites of regional football associations, amateur football associations of Ukraine, the Ukrainian Football Association, the International Federation of Football Associations (FIFA) for the period of 2018 -2023 years, methods of mathematical statistics. Results. Quantitative indicators of the representation of teams from regional football associations in the group and final tournaments of the Ukrainian football championships among amateur teams for the period 2018-2023 were analyzed.
Current development trends of amateur football in Ukraine
Дорошенко Е. Ю. - ORCID: 0000-0001-7642-531Х
Keywords: розвиток; футбол; аматори; чемпіонат; асоціація; development; football; amateurs; championship; association